Kandungan Escherichia coli dan Higiene Sanitasi Pengolahan pada Beberapa Pedagang Minuman Es Kelapa di Kecamatan Oebobo Kota Kupang - Mandala, Damelia; Radja Riwu, Yuliana; Toy, Sarci M.; Basri, Muntasir (Timorese Journal of Public Health, 2020)
Young coconut ice drink is one of the snacks known for its delicious taste and its practical and fresh preparation in Kupang. Young coconut ice drinks have the potential to be contaminated so that they can cause food-borne illnesses (food borne diseases). One of the causes is the Escherichia coli bacterium, which occurs because of the hygienic treatment of foods that do not meet the health requirements. This type of research is descriptive by examining the contents of Escherichia coli and the hygiene description of young coconut drinks suitable for street food snacks in the Oebobo district from 17 to 22 July 2019. The research involves grocers and coconut ice-creams, as well as raw materials for the production of water in all young coconut ice drink producers in the Oebobo district. The number of young coconut ice drink producers in the Oebobo district is 10, so the total sample was used in this study. The data collection method uses observational sheets. The results of this study indicate that there are 6 out of 10 positive samples containing Escherichia coli bacteria, based on the Ministerial Decree of the Republic of Indonesia No. 492/Menkes/Per/IV/2010. The presence of Escherichia coli is said to be contaminated. There are 4 out of 10 manufacturers that meet the health requirements for food handling, equipment, water, food ingredients, additives and service, outlets and dealer centers, based on the Health Minister Decree No. 942 / MENKES / SK / VII / 2003 of the Republic of Indonesia in Terms of hygiene food for snacks.